Cyclic-AMP response element binding protein (CREB) in the neutrophils of depressed patients - Ren, Xinguo (2010)
Cyclic-AMP response element binding (CREB) protein regulates the expression of many genes involved in the pathophysiology of depression. Increased CREB levels were found in the brain of antidepressants-treated rats and decreased protein and mRNA expression of CREB was reported in the postmortem brain of depressed suicide victims. We determined CREB protein expression, using Western blot technique, and CRE-DNA binding, using gel shift assay, in neutrophils obtained from 22 drug-free patients with major depressive disorder (MDD) and 23 normal control subjects. Diagnosis of patients was based on DSM-IV criteria; severity of illness was rated by Hamilton Depression Rating Scale (HDRS). We found that the CRE-DNA binding activity and CREB protein expression was significantly decreased in the neutrophils of drug-free MDD patients compared with normal control subjects. Our findings suggest that CREB may play an important role in the pathophysiology of depression and that it may be an important target for the therapeutic action of antidepressant drugs. Neutrophil CREB levels may also serve as a useful biomarker for patients with MDD.